Article 370: Abrogation and Its Implications - Muhammad Faisal (CISS Insight Journal, 2014)
Article 370 grants a special status to disputed territories of the State of Jammu and Kashmir (J&K), under Indian control, in the Indian Union, and regulates the relationship between India and the State. But Bhartiya Janta Party (BJP) seeks to completely integrate the state of J & Kinto the Indian Union and extend full constitutional framework to it. Consequently, if a BJP led government in India indeed amends or abrogates Article 370 it will have far reaching implications on the nature of dispute as it will transform the relationship between India and the people of J&K. It will change the role of India as party to the dispute. Moreover, it will also undermine the commitments India had made at the United Nations, when it referred the dispute to the world body, and agreed to abide by the UN Security Council resolutions. The BJP has, in last few decades, made abrogation of Article 370 from the Indian Constitution one of its core agenda points. This was evident during election campaign of 2014 when BJP led by current Prime Minister of India Narendra Modi called for debate on, and eventual abrogation of Article 370 from the Indian Constitution. BJP’s opposition to Article 370 goes back to early 1950s when Dr. Syama Prasad Mookerjee, leader of its predecessor party Bharatiya Jana Sangh (BJS) had opposed Indian National Congress led by Jawaharlal Nehru to grant Kashmir the special status with its own flag and then a Prime Minister. He termed the arrangement as further division of India as it gave rise to prospects of self-rule and even independence. Thus, full integration of J&K remained political objective earlier of BJS and now of BJP. In 1990s, BJP also called for abrogation of Article 370 and its manifesto for election 2014 also advocated the same.